Modèles artificiels en plâtre polychromé, étude et restauration - Florian Gaget (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Artificial anatomical models in polychromed plaster were aimed at faithfully reproducing the dissections studied at the National History Museum of Paris during the XIXth century. This study has allowed us to specify their history, the functions and techniques that were used by the casters and painters to realize them. The restoration choices were based on the elements discovered as well as the requirements due to natural history collections.